Reconceptualizing design research in the age of mobile learning. Issue 5 (3rd July 2016) - Bannan, Brenda; Cook, John; Pachler, Norbert
Abstract : The purpose of this paper is to begin to examine how the intersection of mobile learning and design research prompts the reconceptualization of research and design individually as well as their integration appropriate for current, complex learning environments. To fully conceptualize and reconceptualize design research in mobile learning, the authors address and unpack the unique affordances of mobile learning and implications for design research as well as the design process that has impact on both. Asserting a socio-cultural view of learning, investigating mobile devices as cultural transformational tools is proposed to potentially expand perceptions and access to resources not only in how we view teaching and learning (as a form of social capital), but also in how we design for it and conduct research in complex settings.